Coping with cancer pain: a qualitative study to explore pain perception and self-coping strategies of patients with cancer in Sri Lanka - Thamara Amarasekara; N P Edirisinghe; P T R Makuloluwa; C S E Goonewardena (BMJ Open)
Objectives This study explores the pain perception and coping strategies used by patients with cancer pain in Sri Lanka.Design A descriptive qualitative study.Setting Pain management unit, Apeksha Hospital, Maharagama, Sri Lanka.Participants The study was conducted among purposively selected patients with cancer and registered at the pain management unit. 21 semi-structured interviews were conducted until data saturation. Data were analysed using Graneheim and Lundman’s content analysis method.Results Most participants were between 51 and 60 years old and identified as Sinhalese Buddhists. The study’s findings revealed two subthemes under ‘Understanding pain’, namely ‘Physical and emotional impact’ and ‘Cultural and spiritual interpretations’, and five subthemes under ‘Coping strategies for living with pain’, namely ‘Medication and self-control’, ‘Seeking spiritual support’, ‘Receiving social support’, ‘Exploring alternative treatments’ and ‘Adapting daily life’.Conclusion Coping strategies were adopted especially in achieving essential life aspirations and participating in preferred activities. Goals or activities were often adjusted to fall within their health limits. Acceptance and progress in life were considered more important than pain control. We recommend giving due consideration to the ‘self-coping strategies’ of individual patients in designing interventions to mitigate cancer pain.